2004
DOI: 10.1002/qua.20012
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanical studies of isomeric and conformeric structures of methyl‐chloro‐peroxide

Abstract: Ab initio quantum mechanical studies are carried out for the isomeric structures and the torsional potential of methyl-chloro-peroxide. These species are important intermediates in the atmospheric reactions of methyl, methoxy, and methylperoxy radicals with chlorine dioxide, chlorine monoxide, and atomic chlorine, respectively. The calculations indicate that the peroxide form, CH 3 OOCl, with a skew geometry for C, O, O, and Cl atoms, is the lowest minimum energy structure followed by CH 3 OClO. The CH 3 ClO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Thus, CH 3 IO 2 is higher located than CH 3 OOI at the MP2 level by 44.2 kcal mol -1 with basis set A, 10.9 kcal mol -1 with basis set B, and 18.5 kcal mol -1 at the CCSD(T)/B level in agreement with the corresponding XClO 2 , XBrO 2 species, whose stability has been found to depend strongly on the electronegativity of the X partner (13,14,21,(24)(25)(26). The results are consistent with the relative stability order of the HIO 2 isomer, which is also the most unstable in the HOOI family, calculated to be 26.5 kcal mol -1 higher compared to the peroxide isomer HOOI.…”
Section: Electronic Energy and Relative Stability Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Thus, CH 3 IO 2 is higher located than CH 3 OOI at the MP2 level by 44.2 kcal mol -1 with basis set A, 10.9 kcal mol -1 with basis set B, and 18.5 kcal mol -1 at the CCSD(T)/B level in agreement with the corresponding XClO 2 , XBrO 2 species, whose stability has been found to depend strongly on the electronegativity of the X partner (13,14,21,(24)(25)(26). The results are consistent with the relative stability order of the HIO 2 isomer, which is also the most unstable in the HOOI family, calculated to be 26.5 kcal mol -1 higher compared to the peroxide isomer HOOI.…”
Section: Electronic Energy and Relative Stability Resultssupporting
confidence: 74%
“…The third isomer CH 3 IO 2 with a C s symmetry, presents the I-O multiple bond characteristics more enhanced because of the double pair of electrons that are shared with the terminal oxygen atoms. Thus, it presents the shortest I-O bond distance (1.807 Å with basis set A and 1.749 Å with basis set B) following the same trend as all X-O distances in the analogous YXO 2 , X = Cl, Br structures (13,14). The nature of the hypervalent halogen-terminal oxygen multiple bonding has been analyzed in great detail by Lee et al (21) and it has found to present important consequences not only in the bond distances, but in the relative stability of the isomers as well, as we shall see in the next section.…”
Section: Geometry and Frequency Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Indeed, an increasing stability associated with X-ClO 2 and X-BrO 2 compounds has been observed as the electronegativity of X fragment increases and the effect has been demonstrated explicitly for a number of halogen polyoxide families [38][39][40].…”
Section: Structural and Frequency Resultsmentioning
confidence: 99%
“… (a) Reference [37], (b) reference [16], (c) reference [36], (d) reference [22], (e) reference [39], (f) reference [17], (g) reference [44], (h) reference [29], (i) reference [40], (j) reference [25], (k) reference [45], (l) reference [48]. …”
Section: Figurementioning
confidence: 99%